(untitled) (Journal of Plant Disease Sciences, 2020)
In recent years, interest in exploitation of intrinsic potential of the soil crop system to manage the pathogens as in suppressive soils has gained grounds over the relatively unreliable control with conventional methods and concerns about pesticide residues. Suppressiveness of 54 soil samples from the states of West Bengal, Assam and Nagaland was maximum during summer season. Of the soil samples only 12.50% samples from Nadia district of West Bengal showed strong suppressiveness against Sclerotinia sclerotiorum with maximum inhibition of 25.39±26.80. Physico-chemical properties showed that the soils from West Bengal were neutral to slightly alkaline with pH of 6.90±0.68 and exchangeable cation (EC) of 0.21±0.09µs/cm. The soils from Assam and Nagaland were acidic with pH of 5.59±0.49 and 5.22±0.33 respectively. Among the soil biological parameters, microbial activity (FDA hydrolysis), MBC, population of Pseudomonads and actinomycetes were found to be the most important predictor of soil suppressiveness against S. sclerotiorum. These four soil biological parameters conjointly could able to explain nearly 74.2 % of variation of soil suppressiveness against S. sclerotiorum.